Positive psychology to flourish professional well-being: A qualitative study of Indonesian English teachers’ perspective - Nadlifah, Khumrotun; Setiawan, Slamet; Munir, Ahmad (JEES (Journal of English Educators Society), 2023)
A qualitative study has been conducted to explore and encourage Indonesian EFL teachers’ professional well-being using positive psychology. It used thematic analysis approach to scrutinize participants’ well-being and their perception of PP toward their teaching practices during the covid 19 outbreak. By having 4 participants, CATI (Computer Assisted-telephone Interview) was administered to do a semi structured interview since the mobilization was still low during the pandemic. The analyses disclosed that the 5 pillar components of PP or known as PERMA, namely, positive and negative emotions, engagement, relationship, meaningfulness, and achievement were found in participants’ responses to flourish their professional well-being. The results highlight that some elements of PERMA such as accomplishments and meaningfulness are not obtained yet since the participants are still in the process of achieving their most significant goals in their teaching career. Nevertheless, the other three elements, namely, positive emotion, engagement and relationship depicted clearly that all of them are stronger predictors in fulfilling their professional well being. Moreover, the distinctive learning environment, years of teaching, institutional policies and participants’ L1 did not show significant differences on how participants nurture their professional well-being. Thus, it is underlined that an EFL teacher’s professional well-being is not only acknowledged as a personal and subjective occurrence, but it is also influenced by collective and social phenomena in the EFL teacher’s teaching environment. Implications and profound understandings were discussed in this study. HIGHLIGHTS: The analyses disclosed that the 5 pillar components of PP or known as PERMA, namely, positive and negative emotions, engagement, relationship, meaningfulness, and achievement were found in participants’ responses which flourish their professional well-being. The distinctive learning environment, years of teaching, institutional policies and participants’ L1 did not show significant differences on how participants nurture their professional well-being. Higher professional well-being of an educator can contribute to greater work performance by providing teachers with a sense of purpose, meaning, and fulfillment in their work.